Fenomena Flexing Di Medsos : Dampaknya Pada Hubungan Sosial dan Ekonomi: The Phenomenon Of Flexing On Social Media: Its Impact On Social And Economic Relations - Nur Wahidah, Jumaiyah; Khodijah, Khodijah (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
The flexing phenomenon on social media can increase a person's popularity in forming a self-image. Social media has developed into an important platform for developing their reputation and popularity in the modern digital era. The practice of